THE RELATIONSHIP OF KNOWLEDGE ABOUT PARTOGRAPH WITH PARTOGRAPH FILLING IN LEVEL III STUDENTS AT AKBID INDRAGIRI RENGAT - Sari, Desi Intan; Wulandhari, Yopi; Rismawanti, Venny (JURNAL IBU DAN ANAK, 2020)
Abstract How to fill in the partograph is very important to know the signs of earlycomplications in labor. The purpose of this study was to determine therelationship between knowledge of the partograph by filling in the partographon midwifery students Indragiri level III at the Indragiri Midwifery Academy.Analytical design with cross sectional approach with the sampling technique wastotal sampling. The results showed that most or 10 of the 56 respondents(100%) had good knowledge and filled out the partograph completely, while 0out of 56 respondents (0%) had less knowledge and filled out the partographcompletely. Most or 42 of the 56 respondents (91.3%) have good knowledgeand fill in partographs incompletely, while a small proportion or 4 of the 56respondents (8.7%) have less knowledge by filling in an incomplete partographthe conclusion of this study is There was no significant relationship betweenknowledge by filling in the partograph of the student AKBID Indragiri Rengatwith a P value> 0.05.